Etapas de cambio de conducta en relación con la actividad física: motivaciones y barreras para realizarla (2020)
Health promotion is understood as the process that allows people to increase control over the determinants of health and, consequently, improve (Vidarte, et al., 2011, p. 212). According to these authors, physical activity is a very effective strategy to use as an intervention and promote not only physical but also mental health. According to Valdés (1996, cited in Azofeifa, 2006), motivation is one of the most important aspects for good performance in any activity, and it works as a regulating factor of energy and emotion used to meet goals. In this order of ideas, there is a model proposed in 1994 by Proschaska and DiClemente that can help to understand the process of change in people's behavior and identify what stage and process of change they are in: the transtheoretical model of behavior change (Klcokner, 2015). The stages assume a temporal dimension, while change can take place, while the processes...